Innovation In Public Policy Development: Challenges And Opportunities For Public Administration - suhindarno, Heny; Katili, Andi Yusuf; Nggilu, Rukiah; Irfansyah, Irfansyah (PT. Anagata Sembagi Education, 2024)
The phenomenon of globalization requires the government to continue to innovate in public policy in order to respond to rapid social, economic, and technological changes. This study focuses on the challenges and opportunities in implementing public policy innovation in Indonesia. The approach used is the Systematic Literature Review (SLR), which analyzes literature from the last 10-15 years related to innovations such as e-government, big data, and cross-sector collaboration through Public-Private Partnership (PPP). The results of the study show that public policy innovation can increase bureaucratic efficiency and public participation, especially through digital platforms that enable direct interaction between the public and the government. However, the implementation of this innovation faces a number of challenges, such as bureaucratic resistance to change, limited human resources, and the digital divide in various regions of Indonesia. Local governments are often less prepared to adopt new technologies due to limited infrastructure and lack of skills in managing big data and other digital technologies. The conclusion of this study emphasizes that bureaucratic reform and increasing human resource capacity are urgent needs to ensure the successful implementation of innovation in public policy. In addition, closer collaboration between the government and the private sector through mechanisms such as PPP can help accelerate infrastructure development and improve the quality of public services. The implications of this study indicate that the government needs to be more proactive in encouraging synergy between stakeholders, as well as developing a more equitable and inclusive digital infrastructure to support the sustainability of policy innovation in the future.